KEEFEKTIFAN PELATIHAN GURU TAHU UNTUK MENINGKATKAN TEACHER WELL-BEING PADA GURU SEKOLAH DASAR INKLUSI - Berliana, Azirna Berliana; Nugraha, Sumedi P. (Universitas Islam Indonesia, 2024)
Inclusive school teachers are required to have adequate preparation to conduct optimal teaching processes for students with disabilities. Such preparations lead to work pressure and negative emotions, resulting in low teacher well-being. This study aimed to enhance the teacher well-being of inclusive elementary school teachers through the